DIAGNOSTIC ACCURACY OF (FNAC) BIOPSY IN PALPABLE MAMMARY LESIONS (Iraqi Journal of Medical Sciences, 2016)
Background:Fine Needle Aspiration Cytology (FNAC) has advantage of providing a diagnosis before the time of surgery; this situation enable the patient and surgeon to discuss and decide the type of surgery to be done and may obviate the need for a 2 stage procedure in surgical management of breast cancer.Objectives:To study the accuracy, sensitivity and specificity of FNAC of solid breast mass compared to histopathological examination.Methods:A retrospective study includes 126 female patients palpable solid breast mass aged 17 to 67 years with masses in the breast. FNAC and histopathological studies was done to all of them.Results:Fifty six patients had mass in the Rt. Breast and 70 (57.4%) had mass in the Lt. breast. 58 (47.5%) masses diagnosed as malignant (54 true-positive and 4 false negative) with diagnostic accuracy of 93% (54 of 58). Sixty four patients (52.5%) were diagnosed as benign (62 true-negative and 2 false positive) with diagnostic accuracy of 96.8% (62 of 64).Conclusions: FNAC is simple, quick and relatively low cost procedure, with minimal patient discomfort; it is helpful in reducing the number of breast biopsies done for benign breast disease. It can provide a diagnosis before the time that operation is performed and this may help to obviate the need for two stage procedure in surgical management of breast cancer.Keywords:Solid breast mass, FNAC, Histopathological examination.
Keywords: Solid breast mass; FNAC; Histopathological examination